2017
DOI: 10.1016/j.amjmed.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Disparities in Osteoporosis Screening Among Women in the United States, 2008-2014

Abstract: Despite significant changes in utilization of osteoporosis screening among women ages 50-64 and 80+, in line with national recommendations, tremendous deficiencies among women 65+ remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 15 publications
4
79
1
2
Order By: Relevance
“…Asian populations are prone to have a higher exposure to Cd and Pb (Awata, Linder, Mitchell, & Delclos, ; McKelvey et al, ) and are more vulnerable to have low BMD than other racial groups (Gillespie & Morin, ) regardless of socioeconomic status. Human studies about co‐exposure to Cd and Pb in Chinese adult populations are seldom reported, paritcularly for southwestern areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian populations are prone to have a higher exposure to Cd and Pb (Awata, Linder, Mitchell, & Delclos, ; McKelvey et al, ) and are more vulnerable to have low BMD than other racial groups (Gillespie & Morin, ) regardless of socioeconomic status. Human studies about co‐exposure to Cd and Pb in Chinese adult populations are seldom reported, paritcularly for southwestern areas.…”
Section: Introductionmentioning
confidence: 99%
“…Asian populations are prone to have a higher exposure to Cd and Pb (Awata, Linder, Mitchell, & Delclos, 2017;McKelvey et al, 2007) and are more vulnerable to have low BMD than other racial groups (Gillespie & Morin, 2017) The investigation area of this study is a part of the Chengdu Plain in Sichuan Province, located in southwestern China. The Cd and Pb pollution of soils have been reported in the chosen polluted area (Chen, Teng, Lu, Wang, & Wang, 2015;Zhan, Li, Yu, & Zhang, 2018), and dietary Cd exposure was relatively high owing to homegrown food in adults (Huo et al, 2018).…”
mentioning
confidence: 99%
“…For example, studies have shown that fewer than 30% of women over the age of 65 years with a known diagnosis of osteoporosis receive treatment, and only 23% of women aged 50 years and older who sustain an osteoporotic fracture receive treatment within the first year after fracture . A recent large study that analyzed insurance claims data of more than 1.5 million US women aged 50 years and older found that fewer than 1 in 4 had osteoporosis screening within the most recent 2‐year continuous enrollment period . Osteoporosis screening and treatment rates are even lower for older men in the US .…”
Section: Introductionmentioning
confidence: 99%
“…(15,16) A recent large study that analyzed insurance claims data of more than 1.5 million US women aged 50 years and older found that fewer than 1 in 4 had osteoporosis screening within the most recent 2-year continuous enrollment period. (17) Osteoporosis screening and treatment rates are even lower for older men in the US. (18)(19)(20) One study found that fewer than 20% of men aged 70 to 75 years received screening with dual-energy X-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual utilization of FRAX is poor, with the USA performing 11,807 calculations per 1 million people over the age of 50 [88]. Furthermore, the utilization of any screening method for osteoporosis is less than 27% for patients ages 65-79, with percentages worsening with both younger and older patient populations [89]. Utilization of prescreening methods in a clinical setting could easily increase among physicians, with many other questionnaires and tests available.…”
Section: Denosumabmentioning
confidence: 99%